Computer Based Technical Drawing Practical Competency Training (AutoCad 2022) for Students of SMK 1 Raksana Medan - Sahat; Jandri Fan HT Saragi; Eka Putra Dairi Boangmanalu; Angga Bahri Pratama; Franklin Taruyun Hudeardo Sinaga; Al Qadry (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of PMKM is to provide training and assistance regarding computer-based technical drawing (AutoCad) which is useful for increasing students' competence in drawing. Training and assistance in computer-based technical drawing (Auto Cad) which is useful for increasing students' competence in technical drawing as a preparation for students to enter the world of work and entrepreneurship for vocational school graduates. The method used to resolve the problems that occurred was to use a survey method at SMK 1 Raksana Medan to obtain PMKM data, then the PMKM team formulated training materials, created a training implementation schedule related to time, arranged instructors who would provide training, created activity evaluation designs. The results of implementing PMKM are: Students understand the basic introduction to using AutoCad and the basic commands used for drawing, especially drawing machine components.